Prevalence of Helicobacter pylori in some patients undergoing upper endoscopy - Gregar, I; Axmann, K; Ehrmann, J; Krátká, J; Doslík, V; Zadrazil, J (Acta Universitatis Palackianae Olomucensis Facultatis Medicae, 1991)
The group of 156 patients undergoing upper endoscopy at the Department of Central Endoscopy, University Hospital in Olomouc was followed up for determination of HP status by means of the methods of culture, microscopic examination and determination of specific IgG antibodies by ELISA method. Prevalence of HP was determined in individual groups of the series under study (peptic gastroduodenal lesion, antral gastritis of type B, duodenitis) and in subjects with normal endoscopic finding. The most frequent HP positivity was established by the method of specific antibodies determination by ELISA, then microscopic evidence of HP and finally culture. In the whole series under study HP positivity was found in 59.6% (bacteriology) and 79.8% (ELISA method). The highest HP bacteriological positivity was recorded in antral gastritis of type B (87.1%), or 100% (ELISA method). Individuals with normal endoscopic finding were HP positive in 24.2%, by serology in 38.8%. The group of 25 dialyzed patients with chronic renal insufficiency was HP positive in 28%, by serology in 53.3%.
Keywords: dospělí; nemoci žaludku; Helicobacter pylori; Female; Prevalence; Adult; ženské pohlaví; endoskopie; lidé; Duodenal Diseases; nemoci duodena; Incidence; prevalence; Male; incidence; Esophageal Diseases; Endoscopy; nemoci jícnu; lidé středního věku; Stomach Diseases; mužské pohlaví; Helicobacter Infections; Middle Aged; infekce vyvolané Helicobacter pylori; Humans